Konsumsi bayam merah + madu dengan kadar haemoglobin ibu hamil trimester III - Santiana, Santiana; Hermawan, Dessy (JOURNAL OF Community Health Issues, 2023)
Background: Hemoglobin (Hb) is an oxygen-carrying protein in red blood cells, which gives red blood cells red color. The measurement of hemoglobin levels from 19578 pregnant women, as many as (89.1%) mothers with Hb levels between 8-11 gr% and as many as 3,823 (10.9%) mothers with Hb levels <8 gr%. Bandar Lampung City from 19578 pregnant women who examined Hb levels, as many as 3260 with Hb levels between 8-11 gr% and 2500 with Hb levels <8gr%. Purpose: Known effect of vegetable amaranthus tricolor mixed with honey and hemoglobin levels in third trimester of pregnancy. Methods: This type of research was quantitative, with a quasi experimental analytic design. The study was conducted on Trimester III pregnant women, objects in the study of hemoglobin levels in Trimester III pregnant women before and after consumption of red spinach + honey juice. The study was conducted in January - March 2019 in the Work Area of Bandar Lampung Way Kandis Health Center. Data collection is done using observation sheets. Results: The average Hb level before giving spinach + honey juice is 10,092 with a standard deviation of 0,8558. The average value of Hb after giving spinach + honey juice was 10.697 with a standard deviation of 0.8295 and t-test > t count = 16,474, p-value < 0.05. Conclusion: There was effect of vegetable amaranthus tricolor mixed with honey and hemoglobin levels in third trimester of pregnancy. For pregnant women can increase knowledge about anemia and how to prevent and cope with anemia during pregnancy. Keywords: Hemoglobin, Anemia, Pregnant Women, Amaranthus Tricolor, Honey Pendahuluan: Hemoglobin (Hb) adalah protein pembawa oksigen di dalam sel darah merah, yang memberi warna merah pada sel darah merah. Hasil pengukuran kadar haemoglobin dari 19578 ibu hamil, sebanyak (89,1%) ibu dengan kadar Hb antara 8-11 gr% dan sebanyak 3.823 (10,9%) ibu dengan kadar Hb < 8 gr%. Kota Bandar Lampung dari 19578 ibu hamil yang di periksa kadar Hb, sebanyak 3260 dengan kadar Hb antara 8-11 gr% dan sebanyak 2500 dengan kadar Hb <8gr%. Tujuan: Diketahui pengaruh konsumsi jus bayam + madu terhadap kadar haemoglobin pada ibu hamil Trimester III. Metode: Jenis penelitian kuantitatif, dengan rancangan analitik Quasi eksperimen. Penelitian dilakukan pada ibu hamil Trimester III, objek dalam penelitian kadar haemoglobin sebelum dan setelah konsumsi jus bayam merah + madu. Penelitian telah dilakukan pada bulan Januari – Maret 2019 di Wilayah Kerja Puskesmas Way Kandis Bandar Lampung. Pengumpulan data dilakukan dengan menggunakan lembar observasi. Hasil: Rata-rata nilai kadar Hb sebelum diberikan jus bayam + madu adalah 10,092 dengan standar deviasi 0,8558. Rata-rata nilai kadar Hb setelah diberikan jus bayam + madu adalah 10,697 dengan standar deviasi 0,8295, dengan t-test > t hitung sebesar 16,474 dan p–value < 0,05). Simpulan: Ada pengaruh konsumsi jus bayam + madu terhadap peningkatan kadar hb pada ibu hamil trimester iii. Saran ibu hamil dapat meningkatkan pengetahuan tentang anemia dan cara mencegah serta menanggulangi anemia saat kehamilan. Kata Kunci: Haemoglobin, Anemia, Ibu Hamil, Bayam Merah, Madu